Downregulation of FAPP2 gene induces cell autophagy and inhibits PI3K/AKT/mTOR pathway in T‐cell acute lymphoblastic leukemia. Issue 2 (22nd November 2021) - Yuan, Tian; Wang, Jinhuan; Shi, Ce; Wang, Yi; Xia, Bing; Xu, Wen; Yang, Hongliang; Yang, Yaling; Ye, Matthew T.; Khalid, Samah; Liang, Yong; Tian, Chen; et al.
Abstract: T‐cell acute lymphoblastic leukemia (T‐ALL) is an aggressive hematological malignancy. Most patients with T‐ALL are treated with high‐dose multi‐agent chemotherapy due to limited targeted therapeutic options. To further investigate its pathogenesis and establish new therapeutic targets, we studied the role of FAPP2, a Golgi protein, that is, highly expressed in T‐ALL, in the growth and function of T‐ALL. We found that T‐ALL cells underwent reduced cell proliferation and sub‐G1 accumulation after knocking down of FAPP2 gene using shRNA systems. Instead, FAPP2 downregulation promoted cell autophagy. The level of autophagy markers, LC3Ⅱ/Ⅰ, Beclin1, and ATG5, was markedly increased, whereas that of P62 decreased after FAPP2 knocking down in T‐ALL cells. FAPP2 knocking down led to the accumulation of LC3 in the cytoplasm of T‐ALL cells as shown by fluorescence microscopy. In addition, the level of PI(4)P and PI(3, 4, 5)P decreased and phosphorylation of P‐AKT and P‐mTOR were downregulated in FAPP2 knock‐down cells. In summary, our results show that decreased expression of FAPP2 inhibited cell proliferation, resulted in the sub‐G1 phase accumulation of T‐ALL cells, and enhanced autophagy of T‐ALL cells, likely mediated by PI(4)P, PI(3, 4, 5)P, and PI3K/AKT/mTOR pathway. Our results provide a new insight into the pathogenesis and development of potential targeted therapy of T‐ALL.